일부 보건계열 학생들의 통합돌봄 융합교육에 대한 인식 및 요구 - 조혜은; Hye-eun Cho; 이지연; Ji-yeon Lee; 한종희; Jong-hee Han (Han'guk Ch'iwisaeng Hakhoe chi, 2024)
Objectives: This was carried out to develop an integrated care convergence curriculum. Methods: An online survey was conducted on 312 public health college students, and frequency analysis, t-test, ANOVA, and chi-square test were conducted. Results: Awareness of convergence education (2.55) and experience of convergence education (10.3%) were low, but those with education experience had high awareness of integrated care and convergence education (p<0.001). The need for education (3.07) and manpower training (3.14) were both high, and the preferred training content was first aid (3.57). Conclusions: Additional research is needed on the development of integrated care convergence curriculum.